The evaluation framework for waqf land administration and management in Malaysia - Salbiah Mokhtar (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Waqf is defined as the act of charity where the donors sustain their property from personal use and share it for the benefits of the public. In Malaysia, the administration and management of waqf land lay under each State Islamic Religious Councils (SIRCs) that acted as legal trustees of waqf land. The SIRCs faces several issues that encompass waqf land development, thus reflect the weaknesses in the administration systems that need an immediate attention. Currently, there are no standard administration and management aspects that guided the SIRCs. The aim of this thesis is to formulate an evaluation framework for the administration and management that is adopted from land administration evaluation framework. The evaluation framework can serve as self evaluation for the SIRC or to the monitoring agency such as the Department of Waqf, Zakah and Hajj (JAWHAR) in order to improve the waqf land administration which eventually, can result in standardised waqf land administration and management throughout Malaysia. The study comprises two methodologies for triangulation and validity purposes. The first one is a content analysis of the literature reviews to identify the waqf administration and management strategies that will be used as evaluation tools. The second method is the analysis of selected case studies that adopts the land administration evaluation framework in order to come out with refined evaluation aspects. The findings from content analysis revealed current and innovative strategies in the administration of waqf land. Meanwhile, analyses of case studies revealed significant strategies practiced by the selected SIRCs that worth emulated by other SIRCs. Both findings are incorporated into a comprehensive waqf land administration evaluation framework. The final stage is to quantify the evaluation aspects by using Goal Achievement Matrix approach. The quantified evaluation framework calculates the score of the selected case studies. The result from the evaluation serves as a great reflection to waqf institutions, where the religious councils will have a better idea on their strength and weaknesses as well as their opportunity and threat from the evaluation framework. Additionally, the proposed evaluation framework provides solutions to the problems since the evaluation aspects listed from the sets of strategies are to improve waqf land administration. Hence, hopefully the evaluation framework contributes to the betterment of waqf land administration and management.